DEVELOPMENT OF PSYCHOLOGICAL IMMUNITY ON THE BASIS OF HARMONISATION OF NATIONAL AND RELIGIOUS VALUES (American Journal of Research in Humanities and Social Sciences, 2024)
This scientific research is aimed at improving historical, social, philosophical, pedagogical, psychological aspects of the development of knowledge of religious studies. Extensive research devoted to the spiritual world of man, rational and irrational relations, also pays special attention to the role of world religions in social life and development, harmony of scientific and religious knowledge, traditional and innovative ideas.